4.0 Technologies and the rise of new islands of innovation in European regions. Issue 10 (2nd November 2021) - Capello, Roberta; Lenzi, Camilla
ABSTRACT: The Fourth Technological Revolution has become a reality and profound changes and restructuring in the markets for 4.0 technologies are taking place with important spatial consequences. The paper demonstrates this statement through an empirical analysis based on an original large-scale patent database covering the creation of all 4.0 technologies across all European NUTS-2 regions in the period 2000–15. Regions exist in Europe characterized by a 4.0 technological leadership achieved in the absence of a strong pre-existing 3.0 technological base. By scaling up the existing technological seeds, these islands of innovation can act as best-practice examples for areas that are still lagging behind from the technological point of view.